Analisa Usability Testing Website Antara Information System Pada LKBN Antara - Besus Maula Sulthon; Tarsudin (STMIK Budi Darma, 2024)
In facing the digital era, Perum LKBN Antara continues to innovate to remain a relevant source of information. The presence of online platforms, news applications, and integration with social media allows Perum LKBN Antara to reach a wider and more diverse audience. Information technology support and modern content management systems are key in maintaining speed and accuracy in delivering news. In addition, in internal aspects, Perum LKBN Antara has successfully implemented an integrated information system, one of which is in the financial sector using the Antara Information System website. The Antara Information System website contributes to organizational efficiency by automating processes related to website management. The integrated Enterprise Resource Planning (ERP) system helps combine back-end operations, such as finance, human resources, and inventory management, with the website. This integration reduces manual work, reduces errors, and improves overall operational efficiency. This study measures the quality of the Antara Information System website through Usability Testing dimensions (understandability, learnability, operability, attractiveness) and user satisfaction variables, namely LKBN Antara employees. The data collection method uses primary data in the form of a questionnaire distributed to 109 respondents. Data processing is done using SPSS. Based on data processing, it can be seen that user perceptions of the variables of understandability, learnability, operability, attractiveness are included in the very good category. Based on the research results, it is found that there is only an influence of the attractiveness variable on user satisfaction. From the research results, it can be seen that the understandability variable provides the largest contribution of 87.22% of the other variables.